EcoPedagogy Model Based on Dukuh Indigenous Ecological Wisdom for Environmental Education in Climate Crisis - Swaradesy, Rufus Goang; Kurniawati; Markhmadova, Zhansaya K.; Hidayana, Iip Sarip; Mawaddah, Hawina Nur; Khairullah, Afif Dzaky (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2025)
This research is motivated by the failure of formal education systems to integrate traditional ecological knowledge into the curriculum, thereby creating a gap between indigenous wisdom values and practices in climate change education. This research aimed to develop an integrated learning model based on the Dukuh indigenous community's ecological wisdom for environmental education in the climate crisis era. A participatory ethnographic approach was employed, involving 38 participants comprising teachers, students, indigenous leaders, and community members. Data were collected through in-depth interviews, focus group discussions, photovoice documentation, and participant observation conducted between March and August 2025 in Kampung Adat Dukuh, West Java, Indonesia. Thematic analysis revealed a sophisticated five-function land management system (tutupan, garapan, larangan, titipan, cadangan) and a pamali governance mechanism with compliance rates ranging from 71% to 92%. A significant implementation gap was identified, where 83% of teachers understood local wisdom values. Yet only 17% systematically integrated them into formal curricula due to structural barriers, including limited ethnopedagogical training (88%), curriculum inflexibility (82%), and pressures from an academic achievement orientation (76%). Based on these findings, the EcoPedagogy Culture model is developed, comprising four interconnected pillars: experiential learning, storytelling, ritual-based learning, and apprenticeship. Student preferences strongly favor experiential approaches (94% positive response) and practical demonstrations (88% engagement), compared to traditional lectures (31% engagement). The model demonstrates that students participating in experiential learning sessions achieve 67% higher retention of ecological concepts compared to classroom-only instruction. This research provides an empirically grounded framework for bridging Traditional Ecological Knowledge and formal education systems, offering pathways for climate change adaptation through revitalization of indigenous ecological wisdom in educational contexts.